Copper‐Catalyzed Coupling Reactions of Aryl Halides and Phenols by 4, 4'‐Dimethoxy‐2, 2'‐bipyridine and 4, 7‐Dimethoxy‐1, 10‐phenanthroline. Issue 44 (28th November 2018) - Zhao, Yingying; Wang, Xiangyong; Kodama, Koichi; Hirose, Takuji
Abstract: Several Cu(I) complexes of 2, 2'‐bipyridines were studied for the catalytic coupling of aryl iodides and phenols and 4, 4'‐dimethoxy‐2, 2'‐bipyridine was shown to be an effective ligand of CuI in 1:2 (CuI:ligand) ratio for the synthesis of a wide range of diaryl ethers (up to 97% yield) using K3 PO4 as base in DMF at 100 °C. The catalysis was highly dependent on the reaction temperature and was successfully applied in the coupling with more attractive and challenging substrates, aryl bromides, at 140 °C in good‐to‐excellent yields (78−95%). Moreover, the heteroaromatic effect for the reaction was studied and gave a comparable result with phenyl group (up to 95% yield). Significantly, a structurally related N, N ‐bidentate ligand, 4, 7‐dimethoxy‐1, 10‐phenanthroline, exhibited better performance for less‐reactive combinations of aryl halides and phenols. Abstract : 4, 4'‐Dimethoxy‐2, 2'‐bipyridine and 4, 7‐dimethoxy‐1, 10‐phenanthroline exhibited excellent performance with CuI for the synthesis of a wide range of diaryl ethers (up to 97% yield) from aryl iodides and aryl bromides with phenols using K3 PO4 as base in DMF at 100 °C and 140 °C, respectively.